Low-loss transmission band in photonic crystal waveguides with sharp cutoff at a frequency below the bandgap - Krüger, Asger Christian; Zhang, Min; Groothoff, Nathaniel; Malureanu, Radu; Kristensen, Martin (Optics communications, 2011)
We present TE transmission measurements of photonic crystal waveguides with high hole radius to period ratio r/Λ = 0.388. This geometry introduces a unique low loss transmission band in addition to the traditional PhC guiding band and very sharp transmission edges for devices with a length of 50 μm or longer. Finite difference time domain and plane wave expansion simulations confirm the results and show that the sharpness of the cutoffs can be explained by the spectral shape of the guiding mode in the band diagram. ► New low loss transmission band in photonic crystal waveguides at a frequency below the band-gap. ► Transmission band arises from the large ratio of hole size to lattice period. ► The low frequency transmission band has sharp edges for long photonic crystal waveguides. ► Excellent agreement with 3D FDTD modeling. ► Promising applications in membrane free integrated optical devices where low loss is crucial.